Robust multilevel average controller for trajectory tracking in mobile robots powered by solar panels: Integrating actuators and power electronics stage - Erik Reyes-Reyes; Benjamin Natanael Santiago-Nogales; Josué Roberto Rodríguez-Cerón; Ramón Silva-Ortigoza; Alfredo Roldán-Caballero; José Rafael García-Sánchez; Magdalena Marciano-Melchor; Hind Taud; Salvador Tavera-Mosqueda (Results in Engineering)
This paper addresses the challenge of bidirectional trajectory tracking, for the first time in the literature, in wheeled mobile robots (WMRs) powered by renewable energy by thoroughly considering all involved subsystems. A comprehensive robust multilevel average controller is developed, utilizing the mathematical models of the WMR's mechanical structure, actuators, and power stage. At the mechanical-level, a kinematic control is implemented to ensure precise trajectory tracking. The actuator-level control incorporates two controllers based on differential flatness theory, managing the dynamic behavior of the actuators to achieve smooth and efficient motion. Finally, the power-stage-level employs two additional controllers, also based on flatness theory, dedicated to the power stage subsystem. The effectiveness of the proposed robust controller is experimentally validated using: A differential WMR prototype and a B&K Precision PVS60085MR for replicating the characteristics of a commercial photovoltaic (PV) panel. System integration is facilitated by the DS1104 control board and implemented using MATLAB/Simulink software for real-time operation. The experimental results demonstrate the multilevel average controller's robustness and reliability, highlighting its capacity to maintain precise bidirectional trajectory tracking even in the presence of sudden changes in system parameters.